Regional Autonomy and the Governance of Private Madrasahs in Central Lombok - Baiq Ulfahani, Ahyar, Saparudin (Lembaga Bale Literasi, 2025)
This study aims to analyze the implications of regional autonomy policy on the governance of private madrasahs in Central Lombok Regency. Regional autonomy grants broad authority to local governments in managing the education sector; however, the position of madrasahs under the Ministry of Religious Affairs creates a distinct dynamic in its implementation at the local level. This research employs a qualitative approach with a case study design based on document analysis. Data were obtained from national and regional regulations, regional development planning documents, education budget reports, and madrasah statistical data. The data were analyzed using content analysis techniques and a policy analysis framework covering the background, substance, and implications of the policy. The findings show that regional autonomy has not yet fully strengthened the governance of private madrasahs due to the limited fiscal and regulatory authority of local governments over madrasahs. Although there are opportunities for collaboration and support from regional education programs, implementation is still influenced by the dualism of authority between local governments and the Ministry of Religious Affairs. This study recommends strengthening institutional synergy and affirmative policy schemes to improve the effectiveness of private madrasah governance at the local level.